Investigating the preparation and perspectives of eight high performance athletes. - Werthner-Bales, Penny C (University of Ottawa (Canada), 1998)
The objectives of this research are twofold. The first objective is to complement and extend our knowledge of the psychological mindset that high performance athletes bring to their training and competitive setting that enables them to perform their best. The second objective is focused on achieving a better understanding of the thirty-seven to fifty percent of an athlete's life that is spent outside of physical training and rest/sleep portion of her or his life. To this end, the research studied the lives, thoughts and emotions of eight high performance athletes who had already won medals at the international and Olympic level and were continuing to train for the next Olympics. A three phase process of interviews was conducted with each of the eight athletes and encompassed training, training camps, national trials, international competitions and a 1997 World Championships, over a nine-month period, from December, 1996 to August, 1997. Ten general dimensions were developed that captured the complexity of the lives of the eight athletes. Within the first general dimension, Mental Mindset, a model was developed, in collaboration with the eight athletes. The nine other general dimensions that developed over the course of analysis were Beginnings, Personal Description, The Ebb and Flow of Self Confidence, Meaning of Excelling in Sport, Will, Degrees of Balance, Joy's in an Athlete's Life, Relationships, Difficulties and Dilemmas, and an eleventh dimension, a special case of A Girl on Boys' Teams. Three of these dimensions, Ebb and Flow of Self Confidence, Will and Degrees of Balance emerged from the words and thoughts of the athletes over the course of the three phases of interviews. The other six dimensions were introduced by the researcher in the initial framework. Along with the ten general dimensions, was a sense that each of these athletes were 'living with excelling.' There were both commonalities among the athletes and a uniqueness in the way each of the athletes viewed her or his journey in high performance sport and in life outside of sport. This sense of uniqueness included a 'fierce intensity' that five of the athletes brought to their lives in sport; a 'sense of fragility' that one of the athletes brought to his life, particularly in terms of his level of self-confidence; a 'reflective' manner that was the essence of one of the athletes; and a simple, 'uncomplicated' manner and view of life that was the essence of the eighth athlete. The commonalities included getting an early start in sport (for most but not all); a strong sense of belief, self-confidence and will, when they were performing well; considerable support from others; joy inside and outside the world of sport; learning to accept the inevitable ups and downs and difficulties; and finally, finding a degree of balance in their life. (Abstract shortened by UMI.)
Keywords: Psychology, Behavioral.; Recreation.